"Instamatic living rooms of sin": pornography, participation and the erotics of ordinariness in the 1970s. Issue 2 (3rd April 2022) - Mechen, Ben
ABSTRACT: This article considers the shift in 1970s Britain towards a pornography based not only on popular consumption but popular participation too. Focusing on the 'Readers' Wives' genre of magazine features, it suggests that the making of soft-core pornography offered readers the possibility, through home photography, to document a 'liberated' sexual domesticity with growing cultural currency. This process involved the eroticisation of a broader turn to ordinariness in British culture, as well as the public transgression of the zone of sexual privacy carved out by the Wolfenden Report and the liberal sexual settlement of the 1950s and 1960s. The article therefore tracks the emergence in the late twentieth century of a new model of sexual selfhood that could be sparked into being through new ways of looking and being looked at. Especially for women, 'Readers' Wives' linked sexual objectification and subjectification in a new and profound way. Overall, the development of a pornography of participation and a new erotics of ordinariness are framed in the article as constitutive of the sexual visuality of the 'Sexual Revolution'.